Protective Vaccination against Blood-Stage Malaria of Plasmodium chabaudi: Differential Gene Expression in the Liver of Balb/c Mice toward the End of Crisis Phase - Al-Quraishy, Saleh A.; Dkhil, Mohamed A.; Abdel-Baki, Abdel-Azeem A.; Delic, Denis; Wunderlich, Frank (Frontiers in Microbiology, 2016)
Protective vaccination induces self-healing of otherwise fatal blood-stage malaria of Plasmodium chabaudi in female Balb/c mice. To trace processes critically involved in self-healing, the liver, an effector against blood-stage malaria, is analyzed for possible changes of its transcriptome in vaccination-protected in comparison to non-protected mice towards the end of the crisis phase. Gene expression microarray analyses reveal that vaccination does not affect constitutive expression of mRNA and lincRNA. However, malaria induces significant (p<0.01) differences in hepatic gene and lincRNA expression in vaccination-protected vs non-vaccinated mice towards the end of crisis phase. In vaccination-protected mice, infections induce up-regulations of 276 genes and 40 lincRNAs and down-regulations of 200 genes and 43 lincRNAs, respectively, by >3-fold as compared to the corresponding constitutive expressions. Massive up-regulations, partly by >100-fold, are found for genes as RhD, Add2, Ank1, Ermap, and Slc4a, which encode proteins of erythrocytic surface membranes, and as Gata1 and Gfi1b, which encode transcription factors involved in erythrocytic development. Also, Cldn13 previously predicted to be expressed on erythroblast surfaces is up-regulated by >200-fold, though claudins are known as main constituents of tight junctions acting as paracellular barriers between epithelial cells. Other genes are up-regulated by <100- and >10-fold, which can be subgrouped in genes encoding proteins known to be involved in mitosis, in cell cycle regulation, and in DNA repair. Our data suggest that protective vaccination enables the liver to respond to P. chabaudi infections with accelerated regeneration and extramedullary erythropoiesis during crisis, which contributes to survival of otherwise lethal blood-stage malaria.